The prevalence of, and risk factors for developmental delay among children under the at risk surveillance system at united Bulawayo hospitals, Zimbabwe - Madzimbe, Precious (My University, 2022)
Introduction and background: An estimated 30 to 50% of developmental disorders are identified late at school-going age, thus missing the window for early intervention. The aim of this study was to determine the prevalence and severity of developmental delay in children under the ARSS at United Bulawayo Hospitals. Methodology: A descriptive cross-sectional study that systematically sampled 160 babies enrolled in the ARSS between 2019 and 2020. The Bayley Scales of Infant and Toddler Development Third Edition (BSID-III) tool was used to assess cognitive, motor and language domains. Possible risk factors for developmental delay were also noted from caregivers and patient files. Results: Prevalence of 83.7% developmental delay was established in our sample, the majority of whom presented with mild developmental delay. The majority (60.0%) were classified as having delay in ≥2 domains. The most important risk factors in the ARSS associated with developmental delay in cognitive, motor and speech and language domains were neonatal convulsions, (aOR 5.6, p=0.03) and Apgar scores of <5 (aOR 2.6, p=0.02). Being a boy (aOR 7.1, p<0.001) was also an important risk factor for developmental delay in all the three domains. Conclusion: The majority of children in the ARSS presented with developmental delay in all three domains. Children exposed to risk factors had higher chance of having developmental delay. Children with most important risk factors (boys with low Apgar scores and/or neonatal convulsions) should be closely monitored in the ARSS as they have a high chance of having developmental delay in all three domains.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Physiotherapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022